Characteristics of in peripheral blood of 70 hospitalized patients and 8 diarrhea patients with COVID-19 - Wei, Xiao-Yu; Jing, Ding; Jia, Bei; Li, Qing; Zhou, Xia-Qia; Gong, Ming-Feng; Zou, Jing-Bo; Zhang, Qiang; Huang, Wen-Xiang; Tian, Wen-Guang (International journal of medical sciences, 2020)
To analyze the blood test indicators of patients after infection of COVID-19 in Chongqing and analyze the clinical indicators of 8 patients with diarrhea. : From January 26, 2019 to February 13, 2020, 70 patients diagnosed with 2019-nCoV according to the World Health Organization interim guidance for NCP and divided into diarrhea and non-diarrhea groups. The laboratory tests liver and kidney function, blood routine, coagulation function, and immune status. : The study population included 70 hospitalized patients with confirmed CONV-2019. NCP patients (43males and 27 females) with a mean age of 48.57±17.80 (9~82) years and only 4.3% of patients have lung-related diseases. The positive rate of ESR, CRP, PT, IL6, lymphocyte count, GGT, Prealbumin and CD4 was more than 50%. We further analyzed the differences between 8 diarrhea patients and 62 non-diarrhea patients. Among these indicators, only Lymphocyte, CRP, Prealbumin and Cystatin C positive rate is more than 50%. Although there is no statistical difference in GGT, 100% of the 7 patients tested decreased. Our data recommended that the ESR, CRP, PT, IL6, lymphocyte count, GGT, prealbumin and CD4 have important value in the diagnosis of COVID-19, and the decrease of GGT may be an important indicator for judging the intestinal dysfunction of patients.